Degradação de rifampicina através de sistema de fotocatálise com compósito ZnO/MnFe2O4 - Duarte, Filipe da Silva (2022)
In this study, a composite of zinc oxide and manganese ferrite was synthesized using co-precipitation and hydrothermal routes, to be used as photocatalysts in reactions with UV/Vis light source. The synthesized materials were characterized by FTIR, XRD and SEM, where it was possible to verify the efficiency of the syntheses performed, through the identification of the resulting phases, the evaluation of the structural morphology of the particles and analysis of the detachments of the main vibration bonds present in these materials. The composite ZnO/MnFe2O4 was used in photodegradation reactions of the antibiotic rifampicin, with concentrations of 0.20; 0.40 and 0.60g of the catalyst, reactions using pure ZnO as a catalyst were also performed as a comparative parameter of the influence of MnFe2O4 in this system. The composite ZnO/MnFe2O4 showed a maximum percentage of rifampicin decontamination of 74,20% and ZnO, 94,72%, which indicates a positive influence on this process. The solution treated with ZnO/MnFe2O4 was subjected to magnetic field induction for attraction and consequently accelerated removal of the solids present, successfully, compacting for the application of ZnO/MnFe2O4 to be presented as a promising material for decontamination of emerging pollutants through photocatalytic reactions.